Characterization of blood redox status of early and mid-late lactating dairy cows - L. Cigliano; M. Strazzullo; C. Rossetti; G. Grazioli; G. Auriemma; F. Sarubbi; C. Iannuzzi; L. Iannuzzi; M.S. Spagnuolo (Czech Journal of Animal Science, 2014)
The effect of the stage of lactation on blood redox homeostasis of bovine and buffalo cows was evaluated. The investigation was carried out on early lactating and mid-late lactating cows, reared in a farm located in Campania (southern Italy). Plasma concentration of α-tocopherol and ascorbate, the total antioxidant capacity (TAC), glutathione peroxidase (GPx), and superoxide dismutase activities were higher (P < 0.01) in mid-late lactating cows, thus suggesting a higher consumption of antioxidants during early lactation. Plasma concentration of protein-bound carbonyls (PC) and nitrotyrosine (N-Tyr), and the level of lipid hydroperoxides (LPO) were higher (P < 0.01) in early lactating cows, thus suggesting that lipid peroxidation and peroxynitrite production are crucial in determining oxidative modifications in plasma. TAC was positively correlated with ascorbate concentration (P < 0.03), and negatively correlated with PC concentration (P < 0.002), and ascorbate was negatively correlated with PC (P < 0.03) in mid-late lactating group. These findings demonstrate that circulating ascorbate plays a major role in preventing protein modifications induced by carbonyls, and that ascorbate scavenging effect is impaired during early lactation. We calculated a protein oxidative stress index as the ratio (PC + N-Tyr)/TAC multiplied by 100, and we found that this parameter was higher (P < 0.0001) in early lactating cows. Therefore, it could be useful for assessing the extent of protein oxidative damage in relation to the whole antioxidant status. Further, we suggest that the LPO/GPx ratio multiplied by 100 might be used as lipid oxidative stress index in lactating cows. This index was higher (P < 0.0001) in early lactating cows, and might represent a standard parameter for evaluating the lipid damage depending on a deficiency of the enzymatic antioxidant defence. These parameters are proposed for a possible effective description of physiological changes associated with lactation.